'Reflexive Expectations' in EU–China Relations: A Media Analysis Approach*. (14th July 2015) - Zhang, Li
Abstract: To reverse the downturn in and develop EU–China relations requires mutual understanding. However, the opaque nature of Chinese politics makes it difficult to track China's expectations and its changing views of the EU and their relationship. This paper examines the official Chinese media discourse on the EU's 'actorness' and partnership with China. This helps to bridge the gap between international relations and media studies by linking government foreign relations to media discourse. It argues that China's relations with the EU should be characterized neither as a case of a 'Capability–Expectations Gap' (Hill, 1993 ) nor as an 'Expectation Deficit' (Tsuruoka, 2008 ), but should rather be seen as a matter of 'Reflexive Expectations' by China. The media analysis shows that China's changing national identity, interests and perception of the EU's capability at various times and in various situations influence expectations.